Participatory constitutional reforms vs. realization of equal representation of men and women in the parliaments: a study of Kenya, Rwanda and Tanzania - Lihiru, Victoria Melkisedeck (Department of Public Law, 2020)
In this thesis, the constitution-making legal frameworks in Rwanda, Kenya, and Tanzania are examined in relation to how they facilitated public participation in line with Article 25 of the International Covenant on Civil and Political Rights, 1966 and Article13 of the African Charter on Human and People’s Rights, 1986. In line with Articles 4 and 7 of the Convention on the Elimination of All Forms of Discrimination Against Women, 1979, and Article 9 of the the Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa, 2003, the thesis gauges the level and impact of women’s participation in the constitution-making processes in furthering equal representation of men and women in parliaments. Findings contained in this thesis are informed by primary data from international, regional and national legal frameworks relating to participation in political decision-making processes and are supplemented by secondary data from credible reports, journal articles and books. Analysis of the colonial and early postcolonial constitutional formations depicts imposition of the constitutions by the colonial governments in consultation with a few African political elites. Generally, the colonial and early post-colonial constitutionmaking processes were founded on weak legal frameworks, denying the public, including women, the right to take part in constitution-making processes. The onset of international and regional conventions slowly influenced the opening of the constitution-making processes to the public. The 2003 Rwandan Constitution, 2010 Kenyan Constitution, 1977 Tanzanian Constitution and the subsequent stalled 2014 Tanzanian Proposed Constitution were founded on moderate strong legal frameworks allowing some level public participation. In terms of facilitating women’s participation, these frameworks suffered shortcomings in several aspects particularly in composition of constitution-making organs, access of uneducated and rural women and ensuring substantive participation by women. However, the 2003 Rwandan Constitution, the 2010 Kenyan Constitution, the 1977 Tanzania Constitution and the 2014 Proposed Draft Constitution of Tanzania contain equality and non-discrimination provisions. When it comes to women’s participation in parliaments, the definition of equality is equated to a percentage (mostly 30 per cent), which does not represent the meaning of equality. An increased number of women parliamentarians in the Rwandan, Kenyan, and Tanzanian Parliaments, has enabled the legislation of gender sensitive laws and policies in the areas of inheritance, gender-based violence, family law and land rights. However, there are many areas in which women parliamentarians fail to represent the real interests of women. Challenges related to the practice of first-past-the-post and proportional representation electoral systems and the practice of temporary special measures continue to hinder the realisation of equal representation of men and women in parliaments. Rwanda, Kenya, and Tanzania should adopt the equality-based proportional representation electoral system. Short-term recommendations are provided based on the contextual differences and uniqueness of each country under study namely Rwanda, Kenya and Tanzania.